Pulp tissue dissolution when the use of sodium hypochlorite and EDTA alone or associated - Sá, Marcus Vinícius Reis; Vier-Pelisser, Fabiana Vieira; Darcie, Mirena Sonza; Smaniotto, Daniele Geni Rockenbach; Montagner, Francisco; Kuga, Milton Carlos [UNESP] (FapUNIFESP (SciELO), 2011)
Purpose: The aim of the present study was to evaluate the tissue dissolving capacity of various concentrations of sodium hypochlorite either alone or in combination with 17% EDTA. Methods: Eighty bovine pulp fragments were prepared, and their weight was determined using a precision balance. Each pulp fragment was immersed for 2 hours in a solution/mixture that was based on the following groups: G1-saline solution; G2-0.5% NaOCl; G3-1.0% NaOCl; G4-2.5% NaOCl; G5-17% EDTA; G6-0.5% NaOCl+17% EDTA; G7-1.0% NaOCl+ 17% EDTA; and G8-2.5% NaOCl+17% EDTA. The final weight was measured, and the weight loss was calculated. A statistical analysis was performed using either the Student's t-test for paired samples or an ANOVA and Tukey tests (P<0.05 was considered to be significant). Results: We measured a significant difference between the sample weight before and after treatment for each of the tested groups (P<0.05). The 2.5% sodium hypochlorite solution (G4) completely dissolved the pulp tissue within the test period. NaOCl+EDTA was less effective than sodium hypochlorite alone at dissolving the pulp tissue (P<0.05), and EDTA alone (G5) did not markedly dissolve the pulp tissue. Conclusion: Using EDTA together with NaOCl reduced the tissue dissolving properties compared with NaOCl alone, regardless of the concentration of NaOCl that was used. © 2011 Só et al.; licensee EDIPUCRS.
Keywords: EDTA; Endodontics; Pulp tissue; Sodium hypochlorite